Growth of Carbon Nanotubes on Electrospun Cellulose Fibers for High Performance Supercapacitors. Issue 13 (25th October 2017) - Li, Qiang; Deng, Libo; Kim, Jang-Kyo; Zhu, Yanqiu Q.; Holmes, Stuart M.; Perez-Page, Maria; Eichhorn, Stephen J.
Abstract : We report the production of cellulose-derived hybrid carbon nanofiber (CNF)/ carbon nanotubes (CNTs) electrodes for the fabrication of high-performance supercapacitors. The CNTs were grown via a floating catalyst chemical vapor deposition (CVD) method on the top surface of electrospun cellulose-derived CNFs. The morphology of these hybrid CNF/CNTs fibrous structures was investigated using scanning electron and transmission electron microscopy. The development of these carbon structures was characterized using Raman spectroscopy. The electrochemical performance of the devices including cyclic voltammetry (CV), galvanostatic charge/discharge (GCD), electrochemical impedance spectroscopy measurements (EIS), and electrochemically stability was carried out. These hybrid CNF/CNTs electrodes had a high value of specific capacitance of 149 F g −1 at a current density 0.5 A g −1, an increase of 15% compared with pristine CNFs. The BET specific surface area increases from 712 m 2 g −1 to 1211 m 2 g −1 from pristine CNFs to hybrid CNF/CNTs, leading to a specific capacitance (per unit area) of ∼170 mF cm −2 . These supercapacitors also retain 90% of the original capacitance over 1000 cycles, showing an excellent stability. This method of supercapacitor electrode production is suggested as a basis to convert a sustainable cellulosic material into a useful energy storage material.